Telocytes in exercise‐induced cardiac growth. Issue 5 (14th March 2016) - Xiao, Junjie; Chen, Ping; Qu, Yi; Yu, Pujiao; Yao, Jianhua; Wang, Hongbao; Fu, Siyi; Bei, Yihua; Chen, Yan; Che, Lin; Xu, Jiahong
Abstract: Exercise can induce physiological cardiac growth, which is featured by enlarged cardiomyocyte cell size and formation of new cardiomyocytes. Telocytes (TCs) are a recently identified distinct interstitial cell type, existing in many tissues and organs including heart. TCs have been shown to form a tandem with cardiac stem/progenitor cells in cardiac stem cell niches, participating in cardiac regeneration and repair. Although exercise‐induced cardiac growth has been confirmed as an important way to promote cardiac regeneration and repair, the response of cardiac TCs to exercise is still unclear. In this study, 4 weeks of swimming training was used to induce robust healthy cardiac growth. Exercise can induce an increase in cardiomyocyte cell size and formation of new cardiomyocytes as determined by Wheat Germ Lectin and EdU staining respectively. TCs were identified by three immunofluorescence stainings including double labelling for CD34/vimentin, CD34/platelet‐derived growth factor (PDGF) receptor‐α and CD34/PDGF receptor‐β. We found that cardiac TCs were significantly increased in exercised heart, suggesting that TCs might help control the activity of cardiac stem/progenitor cells, cardiomyocytes or endothelial cells. Adding cardiac TCs might help promote cardiac regeneration and renewal.